THE ROLE OF BAITUL MUTTAQIN SHARIA COOPERATIVE IMPROVING THE QUALITY OF MICRO BUSINESS MEMBERS - Nanang Sobarna (Research Collaboration Community (RCC), 2023)
This study was conducted with the aim of analyzing the active role of the Baitul Muttaqin sharia cooperative in improving the quality of member micro-enterprises and to find out the various types of active roles of the Baitul Muttaqin sharia cooperative in improving the quality of member micro-enterprises. The research method used is through a qualitative approach by collecting data through structured interviews, observation and documentation. The results of the study show that the active Baitul Muttaqin sharia cooperative has carried out its role as a sharia cooperative that is able to make the business and economic activities of its members better, while the type of active role that has been carried out by the active Baitul Muttaqin sharia cooperative in improving the quality of micro-enterprises for its members is only in aspects of product marketing and have not touched on aspects of quality service management, product and service product management, financial management and sharia business ethics management.